Evaluation of Different Methods of Zinc Application on Growth, Yield and Biofortification of Zinc in Rice (Oryza sativa L.) - Maneesh Kumar and Omkar Kumar, Ayan Das, S.K. Singh (Journal of the Indian Society of Soil Science, 2019)
Zinc (Zn) fertilization, not only gives better yield of cereals but also provides better nutrition to the population. This study evaluated the effect of different Zn application methods on growth, yield and biofortification of Zn in rice. Zinc treatments included were: soil application (5 kg Zn ha-1) (SA), root dipping (2% ZnO slurry) (RD), foliar spray (0.5% ZnSO4.7H2O + 0.25% lime) at tillering and milking stage (FS) and combinations of these treatments. Significantly higher grain yield was obtained in SA + RD + FS and RD + FS (27.2 and 22.6% increase over RDF, respectively). Zinc content in grains had a significant positive correlation with grain yield (r = 0.395, p< 0.05). Efficiencies of applied Zn decreased with increasing Zn application rates, except crop recovery efficiency. Maximum Zn content in grains and bioavailability of the fortified Zn was recorded in SA + FS treatment. However, less than 1% of the fortified grain Zn was bioavailable. Zinc enrichment had a negative (p< 0.01) impact on Fe content in both grain (r = -0.538) and straw (r = -0.603), but showed a positive (p< 0.01) correlation in respect of Mn content in grain (r = 0.556).